The Organizing Model and the Management of Change: A Comparative Study of Unions in Australia and Britain - Carter, Bob; Cooper, Rae (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2002)
SummaryTrade unions in nearly all developed countries are facing major difficulties in maintaining membership levels and political influence. The U.S. labour movement has been increasingly attracted to an organizing model of trade unionism and, in turn, this response has caught the imagination of some sections of other Anglo-Saxon movements, most notably in Australia, New Zealand and Britain. Despite similarities in the problems that national union movements face, however, the histories and current experiences of trade unions in the various countries show marked differences. This article, based on extensive fieldwork in Britain and Australia, examines attempts to assess the importance of national contexts in the adoption of the organizing model through a comparative study of an Australian and a British union.